The Impact of Tax Audit Intensity and Probability of Fraud Detection on Tax Evasion: The Moderating Role of Tax Officials' Service - Ahmad Bukhori Muslim; Dian Sulistyorini wulandari; Ita Sari (Journal of Scientific Interdisciplinary, 2024)
This study investigates the relationships between tax audit intensity, the probability of fraud detection, and tax evasion while examining the moderating role of tax officials' service. The research reveals that tax audit intensity significantly reduces tax evasion, confirming its effectiveness as a deterrent. However, the hypothesis regarding the probability of fraud detection's impact on tax evasion was rejected, indicating that the likelihood of detection does not directly influence taxpayer behavior in this context. Additionally, the study found no significant moderating effect of tax officials' service on the relationship between tax audit intensity, fraud detection probability, and tax evasion. These findings suggest that while audit intensity is crucial for enhancing compliance, the quality of service provided by tax officials does not substantially alter taxpayer responses to enforcement measures. The results underscore the need for tax authorities to prioritize strengthening audit processes and detection mechanisms while recognizing that service quality, though important for building long-term trust, may not significantly influence immediate compliance behavior. Future research should explore other moderating factors that could impact taxpayer decisions in varying economic and cultural contexts.